Assessment of the current state of populations and study of phytochemical features of Conium maculatum L. in the Ili-Alatau mountains (International Journal of Biology and Chemistry, 2021)
A comprehensive study of the anatomical structure of the plant Conuim maculatum L. from the genus Ariaceae Lindl., which has valuable medicinal properties is presented. Currently, the medicinal plant Conuim maculatum L. is widely used in folk medicine. This plant is used by specialists for the prevention of various diseases, especially for the treatment of various types of cancer, as well as for the preparation of active painkillers and anti-inflammatory drugs. The article analyzes the current state of the plant Conuim maculatum L. in the Іli-Alatau, diagnostic signs were identified and the main features of its anatomical structure were analyzed. The article analyzes in detail the biological features of the medicinal plant Conuim maculatum L., the main promising distribution zones of the plant in the country, and also describes the systematic classification, phytochemical features and chemical structure of this species. Eco-phytocenotic features of  Conuim maculatum L. are shown on a population growing at the foothills of the Іli-Alatau. The work on determining the chemical composition of the species Conuim maculatum L. was carried out at the research center of medicinal plants of the al-Farabi Kazakh National University.